Genie in the bottle: Gezi Park, Taksim Square, and the realignment of democracy and space in Turkey. (May 2014) - Örs, İlay Romain
Leaving İstanbul Bilgi University on 22 May 2013, conveners of the İstanbul Seminars could not have guessed that less than a week later the arguments they had debated would be revisited under a new light. For little did anybody know that in the summer of 2013 İstanbul would become the stage of one of the most intriguing of urban uprisings in Turkish, if not world, contemporary history. In this article I would like to take up some of the challenges brought up by Gezi resistance to rethink the concept of democracy through the changing ways in which people engage with urban public spaces in Turkey, and beyond.